Temperature Sensitivity Coefficients of RDX‐Based Propellants and Their Mixed Charges. Issue 10 (16th August 2021) - Fu, You; Zhu, Yao; Liu, Zhitao; Xu, Bin; Shen, Jinpeng; Wang, Yingbo; Liao, Xin
Abstract: Low temperature sensitivity coefficients of gun propellants are of great significance for improving the stability of weapon performances. In this work, RDX‐NC‐NG‐DEGDN propellants (R‐MNEGP) were prepared to reduce the temperature sensitivity coefficient of mixed charges. The temperature sensitivity coefficients of R‐MNEGP, NC‐NG‐DEGDN propellants (MNEGP) and their mixed charges were studied by closed vessel tests, scanning electron microscope (SEM), and ballistic firing experiments. The results show that the increased burning surface of R‐MNEGP compensates the decrease in the burning rate of the propellant when the initial temperature is decreased compared with MNEGP. The temperature sensitivity coefficient of R‐MNEGP is lower than that of MNEGP, and the temperature sensitivity coefficients of the mixed charges (R‐MNEGP and MNEGP) are between these two temperature sensitivity coefficients in the range of −40 °C–20 °C and 20 °C–50 °C. Compared with MNEGP, the velocity temperature sensitivity coefficients of the mixed charges with 6 wt % and 10 wt % R‐MNEGP decreased by 34.86 % and 70.67 %, and the pressure temperature sensitivity coefficients of these decreased by 42.99 % and 100.90 % with increasing temperature from −40 °C to 15 °C. And the velocity temperature sensitivity coefficients had no significant change, and the pressure temperature sensitivity coefficients decreased by 2.58 % and 77.98 % in the range of 15 °C–50 °C. This study offers an attractive strategy for tuning the temperature sensitivity coefficient by mixing charges of R‐MNEGP and MNEGP with different temperature sensitivity coefficients. Abstract :